Genealogical Reconstruction of Astabrata: From Feudal Leadership Doctrine to Contemporary Counselor Personality Competence - Wiratsongko, Bayu; Suwarjo, Suwarjo (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
Astabrata, the ancient Javanese leadership philosophy rooted in Hindu traditions, has undergone significant semantic transformation from feudal leadership guidelines to a philosophical framework for contemporary counselor personality development. This study employs genealogical hermeneutics integrating Paul Ricoeur's three-stage textual interpretation to trace Astabrata's transformative dynamics across historical contexts: from classical religious-harmony contexts to feudal bureaucratic power structures, and finally to modern professional counselor development. Through textual genealogy tracking Kakawin Ramayana to Serat Rama Jarwa Macapat (Yasadipura I, 1822) to contemporary applications, this research identifies how eight principles (Indra, Yama, Surya, Candra, Bayu, Kuwera, Baruna, Brama) initially symbolizing ideal leader characteristics can be reinterpreted as representing essential counselor personality attributes. The study demonstrates that this genealogical transformation reflects an epistemological shift from hierarchical power paradigms toward individual care and empowerment paradigms. By integrating classical Javanese self-cultivation concepts (mawas diri, eling waspada, sangkan paraning dumadi) with contemporary counselor competency frameworks, this research contributes significantly to developing culturally-grounded Indonesian counselor education models that recognize personality development as foundational to professional competence. Practical implications include normative framework for counsellor education and philosophical grounding for competency formulation rooted in Javanese philosophy.